The Analysis of Franchise Fee and Royalty Fee Systems in the Business of Nyoklat Klasik™ Based on al-Mu‘amalah al-Maliyah Perspective - Mufti Afif; Asifah Itsna Rosidah; Nur Hidayah Al Amin; Ahmad Suminto (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This study aims to determine the franchise and royalty fees implementation system in the Nyoklat KlasikTM Tulungagung. This study employed qualitative research, specifically field research. Data collection is maintained by using interviews, observation, and documentation. this study uses the descriptive-qualitative analysis method, which describes the implementation of the Franchise Fee and Royalty Fee Systems on Nyoklat KlasikTM, then analysis it from the point of view al-mu’amalah al-maliyah. The result is that the franchise fee payment is not paid fully but will be paid 50% after signing the contract, and the rest is paid before shipping the goods. The chosen place must follow the standards that are set by the franchisor. The royalty fee charged by the franchisor to the franchisee is about 1-3 million per year. The franchisor provides repeat order prices of 45%–50% of the regular price. From the al-mu’amalah al-maliyah perspective, the franchise fee and royalty fee systems of Nyoklat KlasikTM are appropriate with the basic principles of al-mu’amalah al-maliyah, that is: a principle of tauhid; prohibition of riba; prohibition of gharar and maisyir; prompts to trade and share benefits and risks; no time value of money concept; funding is based on tangible assets; compliance agreement.